Adding detailed transmission constraints to a long-term integrated assessment model – A case study for Brazil using the TIMES model - Miranda, Raul (2019)
We thank the Brazilian Federal agencies CAPES (Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior) and CNPq (Conselho Nacional de Desenvolvimento Cientifico e Tecnologico) for their support for the scientific research performed at the Energy Planning Program, Universidade Federal do Rio de Janeiro. We would also like to thank the European Commission for their support to the scientific research performed jointly by the Energy Planning Program and the Center for Environmental and Sustainability Research.